Peran Guru PKN Dalam Meningkatkan Kedisiplinan Siswa Kelas X Melalui Pendekatan Keteladanan Guru Di SMA St. Maria Rubit - Henderika Lany; Petrus Kpalet; Gisela Nuwa (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research aims to determine the role of civics teachers in improving the discipline of class X students at SMA St. Maria Rubit and to find out the teacher's efforts as well as the form or model of teacher example regarding student discipline. This research uses descriptive qualitative methods. The informants in this research were the Principal, Citizenship Education Teacher, and Class Teacher at St. Mary's High School. Maria Rubit. The data collection techniques used were observation, interviews and documentation. Data analysis techniques include data reduction, data display, and data verification. The results of the research show that: The role of civics teachers is very important in improving student discipline at St. Maria Rubit, In accordance with existing school regulations, the aim is to apply discipline so that students can be time disciplined, be on time for school, be disciplined in dressing, be disciplined in attitude and be disciplined in completing assignments. In improving student discipline at school, I give constructive sanctions to students, all school members must comply with school regulations and work together with all school members to improve student discipline. Student discipline at St. Maria Rubit still lacks discipline, because there are still students who do not follow the rules set by the school, for example; time discipline, discipline in dressing and discipline in speaking. Exemplary efforts/forms made by teachers in upholding student discipline are by providing guidance and socializing the importance of discipline. The efforts made by teachers are by providing good examples for students.